Intracortical inhibition is modulated by phase of prosthetic rehabilitation in transtibial amputees - Hordacre, Brenton; Bradnam, Lynley V.; Barr, Christopher; Patritti, Benjamin L.; Crotty, Maria (Frontiers in Human Neuroscience, 2015)
Reorganisation of primary motor cortex (M1) is well described in long-term lower limb amputees. In contrast cortical reorganisation during the rehabilitation period after amputation is poorly understood. Thirteen transtibial amputees and thirteen gender matched control participants of similar age were recruited. Transcranial magnetic stimulation was used to assess corticomotor and intracortical excitability of M1 bilaterally. Neurophysiological assessments were conducted at admission, prosthetic casting, first walk and discharge. Gait variability at discharge was assessed as a functional measure. Compared to controls, amputees had reduced short-latency intracortical inhibition for the ipsilateral M1 at admission (p=0.01). Analysis across rehabilitation revealed short-latency intracortical inhibition was reduced for the contralateral M1 at first walk compared to discharge (p=0.003). For the ipsilateral M1 both short and long-latency intracortical inhibition were reduced at admission (p<0.05) and prosthetic casting (p<0.02). Analysis of the neurophysiology and gait function revealed several interesting relationships. For the contralateral M1, reduced inhibition at admission (p=0.04) and first walk (p=0.05) was associated with better gait function. For the ipsilateral M1, reduced inhibition at discharge (p=0.05) was associated with poor gait function. This study characterised intracortical excitability in rehabilitating amputees. A dichotomous relationship between reduced intracortical inhibition for each M1 and gait function was observed at different times. Intracortical inhibition may be an appropriate cortical biomarker of gait function in lower limb amputees during rehabilitation, but requires further investigation. Understanding M1 intracortical excitability of amputees undertaking prosthetic rehabilitation provides insight into brain reorganisation in the sub-acute post amputation period and may guide future studies seeking to improve rehabilitation outcomes.